(untitled) (Research, Society and Development, 2020)
Sorghum plants are well cultivated in central region of Brazil, which is originalmente low fertility and rich in aluminum content. These features demand studies to know better hybrids for such environment, mainly regarding the use of nutrients like nitrogen (N). This nutrient is the most limiting to plant growth, development, production and for this reason it is of great concern to understand the effects of low bases saturation on N use in biomass dedicated sorghum plants, that is hybrids used for bioenergy purpouses. With the aim to assess the effect of increasing liming rates on nitrogen use in biomass sorghum hybrids we set a greenhouse quantitative research as a completely randomized factorial experiment by using two sorghum hybrids (PA 5L60 and PA 5D61) under five different bases saturation (V%) – 15, 35, 40, 50 and 60. This experimental design allowed us to study five different concentrations of aluminum in this soil. The growth of both sorghum hybrid was impaired only under at V% 15. Nitrogen concentration, content and the N use efficiency indicators were affected at V% 15 for both sorghum hybrids; however, the hybrid PA 5D61 showed to be less sensitive than PA 5L60 under the studied conditions. The PCA analysis showed that the hybrid PA 5D61 showed to be more tolerant to aluminum and uses N more efficiently than the hybrid PA 5L60 and, therefore, we can argue that this hybrid should be used in marginal, low fertility lands as a feedstock producer for bioenergy.